Efecto citotóxico del extracto etanólico de las hojas de Annona cherimola en una línea celular de cáncer de pulmón humano en medio de cultivo con pH ácido - Durán Hernández, Karla del Cisne (2016)
Lung cancer is a malignant tumor that develops from lung and bronchial cells is uncontrolled growth of abnormal cells in the body that damage tissues and organs. Some of these agents, called carcinogenic substances such as nicotine in snuff act on the body and cause damage to the healthy cell. Being a health problem considering the need for this study called "Cytotoxic effect of ethanol extract of leaves annonae cherimola in a cell line of human lung cancer in culture medium with pH acid" and aims verify the cytotoxic activity of chloroform extract with acid pH leaves of Annona cherimola front lines of lung cancer in the Province of Loja. The study of this research will be Experimental design - Prospective, and cell lung cancer line 549. The techniques used to identify the cytotoxic effect of the chloroform extract were cell proliferation and cell viability. And it was concluded that 84% of the concentrated extract killed cancer cells. Keywords: lung cancer cell lines, ethanol extract, proliferation, viability.